The determinants of poverty incidence in selected rurban communities - Mancebo, Samuel T. (USM R & D Journal, 2009)
The study attempted to determine the correlates of poverty incidence in a urban community and identify some appropriate community education, training and other related strategies in reducing poverty incidence. Recommendations were forwarded by the researchers for those concerned to possibly implement in order to reduce the nagging poverty suffered by the people. This research study selected two municipalities: Daet, Camarines Sur representing Region V and Lumban, Laguna for Region IV. In each municipality a sample of 100 households were randomly picked from the rurban and rural barangays of the towns. Surveys and interviews were employed to gather data using open and close-ended questionnaire and likert-type interview schedules. The data were analyzed using descriptive statistics such as frequencies, means and percentages and inferential statistics for qualitative data correlation such as the Rao-Scott and Cramers' V Chi-square tests. Results of the study revealed that both sample communities had a very high percentage of families above the poverty threshold which are even higher than the Philippine average. All sites in the study communities have demonstrated a higher level of attitudinized scores which generally is within the literature definition of poverty. These scores shown by the barangays meant a positive outlook in life to fight their impoverished situation if given the opportunity. The confluence of factors that came out to be strongly associated with a high of living as measures of poverty incidence were age, use of cell phones, institutional factors such as the immediate opportunity to apply for a loan, borrow from private institutions and the availment of educational services particularly for those who had completed college education. It is further concluded that in general the mental attitude of poverty exhibited by the respondents also reflected their definition of poverty which could be reversed through quality education.